Revenue allocation in Nigeria : Review and recommendation (Lagos : Nigeria Government press, 1970)
This review is a detailed compilations of the Nigeria revenue allocation to various sector of the economy with emphasize all tiers of the government.
asm; 10/04/19
Loans
Keywords: Fiscal policy; Revenue allocation; Nigeria